Impact of Gender, Age, and Obesity on Childhood Obstructive Sleep Apnea: A Cross-Sectional Study of 4,668 Children - Huang G; Wang Q; Chang L; Ye S; Liu J; Lu Y; Li T; Zhan X; Liang J; Cheng Y; Gu Q (Nature and Science of Sleep, 2025)
Guimin Huang,1,* Qian Wang,2,3,* Li Chang,4 Siyu Ye,2 Junting Liu,1 Yingxia Lu,2 Tao Li,1 Xiaojun Zhan,2 Jieqiong Liang,2 Yijing Cheng,1 Qinglong Gu2,3 1Child Health Big Data Research Center, Capital Institute of Pediatrics, Beijing, People’s Republic of China; 2Department of Otolaryngology-Head and Neck Surgery, Capital Institute of Pediatrics, Beijing, People’s Republic of China; 3Graduate School of Peking Union Medical College, Beijing, People’s Republic of China; 4Department of Respiratory Medicine, Capital Institute of Pediatrics, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qinglong Gu, Department of Otolaryngology-Head and Neck Surgery, Children’s Hospital, Capital Institute of Pediatrics, Beijing, People’s Republic of China, Email gql71@163.comPurpose: Obstructive sleep apnea (OSA) is a common condition in children, linked to significant health risks. However, the impact of gender, age, and obesity on OSA severity remains poorly understood. This study aimed to explore how these factors influence OSA in pediatric patients.Patients and Methods: This cross-sectional study was conducted at the Sleep Center of the Children’s Hospital Affiliated with the Capital Institute of Pediatrics from January 2017 to May 2023. We included children aged 0 to 15 years diagnosed with OSA via overnight polysomnography (PSG). Demographic data, including gender, age, and body measurements, were collected. The apnea-hypopnea index (AHI) and oxygen desaturation index (ODI) were recorded. Data analysis included one-way ANOVA for continuous variables, chi-square tests for proportions, linear trend analysis for changes across age and OSA severity, and Pearson/partial correlations for associations between BMI, AHI, and other variables.Results: The study involved 4668 children, with a mean age of 5.3 years, 62.3% of whom were boys. Boys had the highest Apnea-Hypopnea Index (AHI) (8.8 ± 7.9). The 0– 2 years age group exhibited the highest AHI (10.7 ± 9.8), while the obese group had the highest AHI (13.9 ± 19.8). Logistic regression analysis revealed that male gender (OR = 1.2, 95% CI: 1.11– 1.43), age 0– 2 years (OR = 1.49, 95% CI: 1.09– 2.04), and obesity (OR = 1.29, 95% CI: 1.09– 1.52) were significantly associated with moderate to severe OSA.Conclusion: This study underscores the complex roles of gender, age, and obesity in pediatric OSA severity. Boys, especially those in the 0– 2 years age group, had more severe OSA than girls, and obesity exacerbated OSA severity. These findings may guide improved screening and management strategies for pediatric OSA.Keywords: pediatric obstructive sleep apnea, age, gender, obesity, severity